2016
DOI: 10.2147/ott.s102422
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin prevents hypoxia-induced epithelial–mesenchymal transition in human breast cancer cells

Abstract: Paeoniflorin (PF) is a monoterpene glycoside extracted from the root of Paeonia lactiflora Pall. Previous studies have demonstrated that PF inhibits the growth, invasion, and metastasis of tumors in vivo and in vitro. However, the effect of PF on hypoxia-induced epithelial–mesenchymal transition (EMT) in breast cancer cells remains unknown. Therefore, the objective of this study was to investigate the effect of PF on hypoxia-induced EMT in breast cancer cells, as well as characterize the underlying mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 30 publications
(27 reference statements)
3
40
0
Order By: Relevance
“…Recently, methods for treating breast cancer have being improved; however, the clinic effects for patients are not satisfactory; therefore, further investigations on treatment methods of breast cancer are necessary to improve the cure rate. Recent in‐vitro studies indicate that Paeoniflorin in various concentrations inhibits expression of HIF‐1α through regulating pathway PI3K/Akt, thus prevent against epithelial‐to‐mesenchymal transition (EMT) which is induced by hypoxia on breast cancer cell . Another study indicates that Paeoniflorin inhibits proliferation and invasion of human breast cancer cell lines MDA‐MB‐231 and MCF‐7 through inhibiting pathway Notch1 .…”
Section: Anticancer Activities Of Paeoniflorin and Its Potential Mechmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, methods for treating breast cancer have being improved; however, the clinic effects for patients are not satisfactory; therefore, further investigations on treatment methods of breast cancer are necessary to improve the cure rate. Recent in‐vitro studies indicate that Paeoniflorin in various concentrations inhibits expression of HIF‐1α through regulating pathway PI3K/Akt, thus prevent against epithelial‐to‐mesenchymal transition (EMT) which is induced by hypoxia on breast cancer cell . Another study indicates that Paeoniflorin inhibits proliferation and invasion of human breast cancer cell lines MDA‐MB‐231 and MCF‐7 through inhibiting pathway Notch1 .…”
Section: Anticancer Activities Of Paeoniflorin and Its Potential Mechmentioning
confidence: 99%
“…Recent in-vitro studies indicate that Paeoniflorin in various concentrations inhibits expression of HIF-1a through regulating pathway PI3K/Akt, thus prevent against epithelial-to-mesenchymal transition (EMT) which is induced by hypoxia on breast cancer cell. [36] Another study indicates that Paeoniflorin inhibits proliferation and invasion of human breast cancer cell lines MDA-MB-231 and MCF-7 through inhibiting pathway Notch1. [37] In 2018, Zhang et al [38] found that Paeoniflorin in low concentration successfully inhibits proliferation and invasion of human breast cancer cell line MCF-7 through inhibiting pathway Notch1, then proved Paeoniflorin's antitumour effect additionally.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The EMT process plays an essential role in cancer progression and the hypoxic environment can stimulate this process, [6][7][8]25 so we investigated the effect of Rab10 down-regulation on hypoxiainduced EMT in thyroid cancer cells. As shown in Fig.…”
Section: Down-regulation Of Rab10 Inhibits Hypoxia-induced Migrationmentioning
confidence: 99%
“…Paeoniflorin upregulated apoptosis of MGC‐803 human gastric carcinoma cells and HT29 human colorectal cancer cells (Chen, Lee, et al, ; Parker et al, ; Zheng et al, ). It inhibited proliferation, invasion, and metastasis of MCF‐7/MDA‐MB‐231 human breast cancer cells and human A549 lung cancer cells (Parker et al, ; Zhang, Yuan, Cui, Xiao, & Jiang, ; Zhou, Wang, Song, & Hu, ). The astragalin contained in P. lactiflora induces apoptosis in A375P and SK‐MEL‐2 melanoma cells (You et al, ).…”
Section: Discussionmentioning
confidence: 99%